ANALISIS PRINSIP KEBIJAKAN DAN PENGELOLAAN MERDEKA BELAJAR - Pangkey, Richard; Turang, Martha Margarietha (DIKSAR : Jurnal Pendidikan Dasar, 2023)
The aim of this research is to determine the implementation of the independent curriculum policy in elementary schools. The research method used is library research (library study) with qualitative methods. Secondary data sources come from 33 national journal articles. The data collection method is the documentation method. The data analysis technique consists of four stages, namely data collection, data reduction, data presentation, and inference. The results of several researchers found that the independent learning curriculum had been implemented in elementary schools (motivating schools). Therefore, it can be concluded that the independent learning curriculum policy has been implemented although it requires several improvements and developments. Research regarding the implementation of the independent learning curriculum is still rare, so it is recommended to conduct further research related to analysis of the implementation of the independent learning curriculum policy, both at school and college levels.